Validação do questionário WHODAS 2.0 (Brasil) para indivíduos com fibromialgia - Barreto, Marina Carvalho Arruda (2017)
Fibromyalgia (FM) is a chronic disease that produces symptoms that can affect the functionality, causing health impact. The specific instrument to evaluate patients with FM is not able to cover all the complexity of the health condition. The World Health Organization Disability Assessment Schedule (WHODAS 2.0) came from the need for an instrument that can assess functionality and disability. Aim: To evaluate the reliability, internal consistency and validity of WHODAS 2.0 for the Brazilian population with FM. Methods: The WHODAS 2.0 was applied in 30 Brazilian individuals with FM. The retest test reliability was verified through the application in two distinct moments, correlated by the Spearman test. Internal consistency was assessed with Cronbach's alpha. The criterion validity was evaluated through the correlation analysis of WHODAS 2.0 with FIQ and SF36. The data were analyzed in SPSS 2.2. The study was approved in the committee of ethics and research of the UFTM. Results: The data of the test retest reliability were satisfactory, in the domains and in the total WHODAS 2.0 (r = 0.802, p <0.05). In the internal consistency, all data presented values greater than 0.76. In the analysis of WHODAS 2.0 with FIQ and SF36 we found moderate correlations (r = 0.421, p = 0.021, r = -0.697, p = 0.000, respectively). Conclusion: WHODAS is a reliable and valid instrument for the evaluation of patients with FM, showing values consistent with the literature.